INVESTIGATING STUDENTSâ WRITING IN SENIOR HIGH SCHOOL IN SINGARAJA: AN ERROR ANALYSIS OF LEARNERSâ USE OF ENGLISH AS A FOREIGN LANGUAGE - I Gede, Widya Suputra; I Ketut, Seken; I Gede, Budasi (Jurnal Pendidikan Bahasa Inggris, 2013)
Entitled âInvestigating Studentsâ Writing in Senior High School in Singaraja: An Error Analysis of Learnersâ Use of English as a Foreign Languageâ, this study attempted to find out (1) the types of errors that students made in their writing, (2) the sources of those errors, (3) and why global errors still committed by students in grade XII. As such, the study was designed as a case study. It was conducted in Science Class XII 7 of SMAN 1 Singaraja and a âwriting projectâ was used to collect the data. In this research, the researcher also used questionnaire and interview to obtain additional data. The results of this study show that a total of 184 errors were made by the students. They can be categorized into five types: omission errors with 77 errors (41%), misinformation errors with 70 errors (38%), misordering errors with 6 errors (3.2%), overgeneralization errors with 4 errors (2.1%), and global errors with 27 errors (15%). The errors were mostly caused by interlanguage factors (65%), while about 35 % of the errors were caused by language transfer. In relation to the language transfer causing the errors, three kinds of transfer were found, namely: interlingual transfer, intralingual transfer, and transfer of learning. In addition, in term of global errors, the researcher found two main factors that cause global errors, namely, over-literal translation and lack of information about the sentence-structure of English and English grammar